The Transition of Women's Ideology in Modern Javanese Literature - Yusro Edy Nugroho (Javanologi: International Journal of Javanese Studies, 2023)
AbstractThis study aims to analyze the struggle for women's idealism in modern Javanese literature. The approach used is ideological hegemony and content analysis methods to classify and analyze data from one classical Javanese literary work and two modern Javanese literary works, namely "Serat Wulang Putri" by Nyai Adisara, Novel "Larasati Modern" by Sri, "Katresnan" by Soeratman Sastradihardja, and "Nona Sekretaris" by Suparto Brata. The results of the study show that the development of women's idealistic thinking begins with an inner strength that is patient and accepts the rights of the husband, to become equal friends with men. In the classical period, a restriction only focused on the domestic realm. Even though the reality of the domestic realm still existed in later times, those who had education, independence, and personal wisdom became part of the renewal process. As for the older generation, there is friction over traditional customs in society. What used to be a fixed standard of action has been adapted by itself along with educational developments and foreign cultural influences.Keywords: Ideology, hegemony, women, Javanese Culture, Modern Javanese Literature.